let V be Z_Module; :: thesis: for KL1, KL2 being Linear_Combination of V
for X being Subset of V st X is linearly-independent & Carrier KL1 c= X & Carrier KL2 c= X & Sum KL1 = Sum KL2 holds
KL1 = KL2

let KL1, KL2 be Linear_Combination of V; :: thesis: for X being Subset of V st X is linearly-independent & Carrier KL1 c= X & Carrier KL2 c= X & Sum KL1 = Sum KL2 holds
KL1 = KL2

let X be Subset of V; :: thesis: ( X is linearly-independent & Carrier KL1 c= X & Carrier KL2 c= X & Sum KL1 = Sum KL2 implies KL1 = KL2 )
assume A1: X is linearly-independent ; :: thesis: ( not Carrier KL1 c= X or not Carrier KL2 c= X or not Sum KL1 = Sum KL2 or KL1 = KL2 )
assume A2: Carrier KL1 c= X ; :: thesis: ( not Carrier KL2 c= X or not Sum KL1 = Sum KL2 or KL1 = KL2 )
assume Carrier KL2 c= X ; :: thesis: ( not Sum KL1 = Sum KL2 or KL1 = KL2 )
then A3: (Carrier KL1) \/ (Carrier KL2) c= X by ;
assume Sum KL1 = Sum KL2 ; :: thesis: KL1 = KL2
then (Sum KL1) - (Sum KL2) = 0. V by RLVECT_1:5;
then A4: ( KL1 - KL2 is Linear_Combination of Carrier (KL1 - KL2) & Sum (KL1 - KL2) = 0. V ) by ;
Carrier (KL1 - KL2) c= (Carrier KL1) \/ (Carrier KL2) by ZMODUL02:40;
then A5: Carrier (KL1 - KL2) is linearly-independent by ;
now :: thesis: for v being Vector of V holds KL1 . v = KL2 . v
let v be Vector of V; :: thesis: KL1 . v = KL2 . v
not v in Carrier (KL1 - KL2) by A5, A4;
then (KL1 - KL2) . v = 0 ;
then (KL1 . v) - (KL2 . v) = 0 by ZMODUL02:39;
hence KL1 . v = KL2 . v ; :: thesis: verum
end;
hence KL1 = KL2 ; :: thesis: verum